(untitled) (Journal of Educational Sciences, 2021)
This problem is now in the field of view of the world’s leading educators and psychologists. The article suggests approaches to the creation of a solid theoretical base that would allow the implementation of psychological and pedagogical support of schoolchildren in possible conditions of distancing in order to create a comfortable psychological environment and maintain the quality of education. The article describes the principles on which the organization of distance learning is based, aimed at reducing the level of anxiety. The principles deduced by the authors are selected from the entire content of the general didactic foundations of learning, taking into account the conditions, goals and objectives of online education. The conclusions made by the authors allow us to determine the features of distance learning, to identify the vectors that form the pedagogical problem associated with the psychological and pedagogical support of the education process at a distance. The developed theoretical framework in the future will allow for a comparative analysis of the features of offline and online ways of organizing the educational process, to determine the tools for diagnosing the results of two forms of learning, to justify a set of measures to create a comfortable psychological environment for the student both individually and in collective formats of the organization. The study of anxiety is becoming today one of the problems that require immediate solutions. Keywords: distance education, principles of teaching, psychological and pedagogical support, organization of training, teacher, student, school isolation anxiety.